Hobbes, Bramhall and the Politics of Liberty and Necessity A Quarrel of the Civil Wars and Interregnum - Jackson, Nicholas D (Cambridge University Press, 2013)
Historians may know that sometime in the seventeenth century the English philosopher Thomas Hobbes debated John Bramhall, Bishop of Derry. But where and what did they debate? And why did they debate the issues they did? It is not difficult to find brief descriptions or summaries of their public debate on free-will; this book provides the first comprehensive account not only of that debate, but also of their private quarrel and hostile relations during both the Wars of the Three Kingdoms and Interregnum. Hobbes and Bramhall argued about much more than ‘liberty’ and ‘necessity’ (free-will and determinism), and the following account offers a detailed historical explanation of their debating those and other issues. By situating their long and acrimonious, private and public, dispute within its contemporary context we may come to view the whole quarrel as a by-product or collateral intellectual skirmish of those rebellions and wars in the British Isles.